The Influence of Competence and Work Motivation on Employee Performance at the Human Resources Training Center in the Ministry of Primary and Secondary Education - Rasya Hermalya Putri; Rio Nardo (Yayasan Edukasi Cakrawala Nusantara, 2026)
This study aims to analyze the influence of competence and work motivation on employee performance at the Human Resources Training Center of the Ministry of Primary and Secondary Education. The research employs a descriptive quantitative approach with data collected through questionnaires distributed to 66 civil servant employees using a total sampling technique. Data were analyzed using multiple linear regression to examine both partial and simultaneous effects. The findings show that competence and work motivation positively and significantly influence employee performance. Among the two, work motivation is identified as the most dominant factor in improving performance. These results highlight the importance of enhancing employee competence through continuous training and maintaining motivation through recognition, incentives, and a supportive work environment to strengthen overall organizational performance